Pemantauan Pertumbuhan dan Perkembangan sebagai Upaya Deteksi Dini Stunting pada Balita di Dusun Bibis Desa Timbulharjo Kapanewon Sewon Kabupaten Bantul - Linda Fitria Nuraini; Delta Rahma Dela; Nining Tunggal Sri Sunarti; Reni Tri Lestari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The human development index needs to be prepared early on. Toddlers are the nation's next generation whose nutritional status must be taken into account. Toddler growth and development is a continuous process starting from the womb until adulthood. Monitoring growth and development in toddlers needs to be done. The aim of this community service is to measure the weight, body, height and developmental status of babies and toddlers to detect stunting early. The method used is direct examination using scales, macrotoa and KPSP sheets